The Role of Minor Parties in Political Competition: Lessons from Ghana's 2012 Elections. (April 2015) - Aidoo, Richard; Chamberlain, Adam
The study of minor parties has largely focused on well-established democracies, even though these political organizations play significant roles in new and emerging democracies. With Ghana as a case study, this investigation provides a theoretical path to understanding the normative role of minor parties in political competition, especially in developing nations with single-member plurality systems. By placing emphasis on the experiences of such parties in Ghana's 2012 elections in the Fourth Republican dispensation, this article examines the value and importance of minor parties in helping to create and maintain stable democracies. In spite of the recognizable obstacles minor parties face, we argue that they nevertheless contribute to the health of a burgeoning democratic culture.